Flexible thermosetting pipe - Mustaffa, Z.B. (Trans Tech Publications Ltd, 2014)
The typified as flexible thermosetting pipe, is a new product, developed initially in response to the need for a non-metallic replacement for steel pipe used for oil and gas productions. This product may use for high pressure down-hole applications in which the pipe could repeatedly transported onto a drum. The proposed pipe comprise an internal thermoplastic layer play as liner and a fluid-tight cover, and one or more dual-helical wounding tape stacks applied to the internal liner for absorbing axial and bending loads. The tape stacks are wrapped helically onto the pipe structure with adjacent gaps between wrappings tape to reduce the pressure integrity of the tubular pipe structure. The composite tape stacks are formed from a plurality of thin tape strips and are bonded to each other within a stack. All the layers are manufactured from composite material consisting of highly noncorrosive epoxied matrix reinforced by long continuous fibers. Thus, the proposed flexible pipe designed to be stand alone with thermoplastic liner over-wound with one or more of an epoxy-based structural thermosetting laminate. To this aim, a straightforward simulations of thermosetting pipe is developed via using ANSYS software. Apart from possessing an accurate operational condition, on account of its simplicity the proposed simulation seems also very suitable for further developing and prototyping purposes. Finally, it has been shown that the proposed thermosetting pipe, which partially attains some classical characteristic of both offshore and onshore pipeline by a different line of reasoning, is may serve as a reference in designing flexible pipe. Â© (2014) Trans Tech Publications, Switzerland.